Biomass Estimation and Carbon Storage in Selected Multipurpose Trees and Common Wild Grasses - Miria, A.; Khan, Anisa Basheer (Indian Forester, 2012)
Uptake of CO2 through plant tissues and storage in the biomass is the principle behind carbon sequestration. Carbon allocation to various parts in a tree differs, with the stem or the trunk being the largest reservoir of plant carbon. With forests dwindling, agro forestry and horticultural crops are occupying large land mass. Open wild grasses with a short life cycle also play a major role as carbon sinks contributing more to the soil organic carbon. The present study is on some common multipurpose trees like ornamental trees, plantation crops which were selected within the university campus. Among the grasses both wild variety and lawn grass were selected for comparison. Peltophorum pterocarpum indicated highest total biomass carbon density (496 Kg/t) and Azadirachta indica has the lowest value (462 Kg/t). The average above ground biomass organic carbon stock in trees was 0.84 t/tree and below ground biomass organic carbon stock was 0.12 t/tree and among the grasses Apluda mutica contributed maximum of 0.280 Kg-2 m of carbon per quadrat and Brachiaria ramose (0.055 Kg m-2 ) had the least.